MEMBENTUK KEDIPLINAN DAN MOTIVASI BELAJAR MAHASISWA: STUDI BERDASARKAN PEMIKIRAN JOHN DEWEY - JUNTAK, JUSTIN NIAGA SIMAN; SETYANTI, ELIANA; ANAKOTTA, ELKA; LESILOLO, HERLY J. (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
Education is something that is planned and planned from an educational person to his students, so that the goals of education can be achieved. Likewise, the education carried out at UKTS as a private campus in Surakarta includes lectures in the SPARK program which carries the concept of Smart, Proactive, Innovative, Collaborative, Christian Values which is expected to bring progress in the field of education. One way to realize student discipline and motivation to learn is to hold morning and afternoon assembly activities with a semi-military "like" model with the hope that students will increase their discipline and motivation to study. The aim of this research is to see whether the discipline and motivation to learn in students can be formed through semi-military education as seen from the literature study of John Dewey's thoughts. The results of the research revealed that students' learning motivation and discipline tend to be low, because students come to study only because they get a scholarship and students also study with compulsion because of the disciplinary process implemented by the campus, which is a mismatch with John Dewey's thinking which emphasizes that education must prepare students to live in society. ABSTRAKPendidikan adalah sesuatu yang terencana dan direncanakan dari seorang pendidikan kepada siswanya, sehingga tujuan dari pendidikan dapat tercapai. Demikian pula pendidikan yang dilakukan di UKTS sebagai kampus swasta di Surakarta mengadalam perkuliahan dalam program SPARK yang mengusung konsep Smart, Proacktive, Innovative, Collaborative, Christian Values diharapkan akan membawa kemajuan di bidang pendidikan. Salah satu cara untuk mewujudkan kedispilinan dan motivasi belajar mahasiswa maka diadakan kegiatan apel pagi dan sore dengan model “mirip” semi militer dengan harapan bahwa mahasiswa meningkat kedisiplinan dan motivasi belajarnya. Tujuan dari penelitian ini adalah untuk melihat apakah untuk membentuk kediplinan dan motivasi belajar mahasiswa melalui pendidikan semi militer dilihat dari studi literatur pemikiran John Dewey. Hasil penelitian terungkap bahwa motivasi belajar dan kedisiplinan mahasiswa cenderung rendah, karena mahasiswa datang untuk belajar hanya karena mereka mendapatkan beasiswa dan mahasiswa belajar juga dengan keterpaksaan karena proses pendisiplinan yang diterapkan oleh pihak kampus, dimana adanya ketidaksesuaian dengan pemikiran John Dewey yang menekankan bahwa pendidikan harus mempersiapkan siswa untuk hidup di masyarakat.